1993
DOI: 10.1111/j.1349-7006.1993.tb02052.x
|View full text |Cite
|
Sign up to set email alerts
|

HTLV‐1‐associated Myelopathy/Tropical Spastic Paraparesis‐like Rats by Intravenous Injection of HTLV‐1‐producing Rabbit or Human T‐Cell Line into Adult WKA Rats

Abstract: We intravenously injected Ra‐1 cells or MT‐2 cells into female adult WKA rats. Spastic paraparesis mainly in the hind‐limbs was observed in 1 out of 2 Ra‐1 cell‐injected WKA rats and in 3 out of 8 MT‐2 cell‐injected WKA rats 20 27 months after injection. The main neuropathological finding was symmetrical white matter degeneration with mononuclear cell infiltration of the spinal cord, similar to that of HTLV‐1‐associated myelopathy/tropical spastic paraparesis (HAM/TSP) patients, and degeneration of nerve roots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Freezing is a state of maintained contracted posture and the decrease of resting/sleeping is possibly a symptom of distress in this pathological condition. These motor abnormalities occurred after 15 months, as also shown by Minagawa et al (3), Ohya (12) and Miyatake et al (13), and with a peak after longer periods, such as 20 months, as shown by our results (2,4,5). The period after 7 months has been pointed out as crucial for molecular events occurring in HAM rats (4,14,15).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Freezing is a state of maintained contracted posture and the decrease of resting/sleeping is possibly a symptom of distress in this pathological condition. These motor abnormalities occurred after 15 months, as also shown by Minagawa et al (3), Ohya (12) and Miyatake et al (13), and with a peak after longer periods, such as 20 months, as shown by our results (2,4,5). The period after 7 months has been pointed out as crucial for molecular events occurring in HAM rats (4,14,15).…”
Section: Discussionsupporting
confidence: 87%
“…Although lymphocyte infiltration was demonstrated in some rats, this finding was not observed universally, as also reported by others (4,5). In addition, the hematological results were also nonspecific.…”
Section: Discussionmentioning
confidence: 44%
“…Wistar-King-AptekmanHokudai (WKAH) rats emerged as a model of HAM/ TSP. HTLV-1-infected WKAH rats develop spastic paraparesis with degenerative thoracic spinal cord and peripheral nerve lesions several months following inoculation (Ishiguro et al, 1992;Kushida et al, 1993). The pathology of rat HAM/TSP differs from that seen in humans.…”
Section: Rat Modelsmentioning
confidence: 99%
“…Although initial experimental infection was achieved with F344 rats, it was later established that there was considerable differences in the response of various rat strains to HTLV-1 infection (Ishiguro et al, 1992;Kushida et al, 1993;Ibrahim et al, 1994). Wistar-King-AptekmanHokudai (WKAH) rats emerged as a model of HAM/ TSP.…”
Section: Rat Modelsmentioning
confidence: 99%
“…For analysis of events in such a latent period, it is necessary to establish an animal model in which the growth of HTLV-1-infected lymphocytes and the host immune system reach a certain balance in vivo. Since HTLV-1 cannot replicate well in mouse cells, a certain strain of rat (17) and SCID mice (27) only have been used as animal models of HTLV-1-related diseases. Mice, however, have a great advantages as model animals, and normal immune reactivity is required to investigate the onset of HTLV-1-related diseases.…”
mentioning
confidence: 99%